Auditoría de Gestión a la Fundación Centro de Desarrollo Indígena "CEDEIN", Parroquia Cajabamba, Período 2022 - Yupanqui Guamán, Nelly Marlene. (2024)
ABSTRACT: A management audit is a systematic and independent process that aims to evaluate the effectiveness, efficiency, and adequacy of management activities within an organization, both public and private. It focuses on analyzing how resources and processes are planned, organized, directed, and controlled to achieve established objectives and goals and verifying compliance with the functions and responsibilities assigned to personnel. MANAGEMENT AUDIT TO THE INDIGENOUS DEVELOPMENT CENTER FOUNDATION "CEDEIN," CAJABAMBA PARISH, PERIOD 2022, aims to conduct a management audit of the Indigenous Development Center Foundation "CEDEIN," Cajabamba parish, period 2022. A qualitative-quantitative methodology was used to carry out the audit. The main results show a lack of reviews and periodic meetings with the highest authority, lack of monitoring and accountability, lack of financial control and training, lack of organizational structure, lack of code of ethics and regulations, lack of focus on continuous monitoring, and lack of training and resources. It is concluded that the audit has revealed areas where the organization must fully comply with applicable laws, regulations, and standards. Therefore, a system of periodic review and monitoring of activities is recommended. Keywords: Management Audit, Foundation, Audit Report, Standards, Regulations.